The Role of Service Quality in Increasing Interest in Using Islamic Mobile Banking in the Digital Era - Ananto Triwibowo; Nur Sya'adi (Nuban Jagadhita Centre, 2025)
Introduction: The rapid development of digital technologies has transformed the banking industry, with mobile banking becoming increasingly prevalent among consumers. Objective: This study examines the role of service quality in increasing customer interest in using Islamic mobile banking services in the digital era. While financial technology continues to develop rapidly, Islamic banking faces the challenge of providing mobile banking services that not only meet technological demands but also comply with Islamic principles. Method: Using a qualitative approach, this study analyses how the dimensions of service quality—reliability, responsiveness, assurance, empathy, and physical evidence (SERVQUAL model)—combined with adherence to Islamic principles, influence the adoption and continued use of Islamic mobile banking applications. Result: service quality has a significant positive impact on customer interest, with reliability and adherence to sharia principles being the most influential factors. Implication: This study provides strategic recommendations for Islamic financial institutions to improve their mobile banking services in an increasingly competitive digital landscape